2012
DOI: 10.1080/13854046.2012.744099
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the MMPI-2 Restructured Form (MMPI-2-RF) and Malingered Neurocognitive Dysfunction Among Non-Head Injury Disability Claimants

Abstract: The current study examined the over-reporting Validity Scales of the MMPI-2 Restructured Form (MMPI-2-RF; Ben-Porath & Tellegen, 2008/2011) in relation to the Slick, Sherman, and Iverson (1999) criteria for the diagnosis of Malingered Neurocognitive Dysfunction in a sample of 916 consecutive non-head injury disability claimants. The classification of Malingered Neurocognitive Dysfunction was based on scores from several cognitive symptom validity tests and response bias indicators built into traditional neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 39 publications
2
23
0
1
Order By: Relevance
“…Nonsignificant trends were also observed for Fs and F-r. Finally, Tarescavage, Wygant, Gervais, and Ben-Porath (2013) found that higher scores on MMPI-2-RF overreporting scales, namely F-r and RBS, were associated with probable and definite Malingered Neurocognitive Dysfunction (MND; Slick, Sherman, & Iverson, 1999) in a large sample of nonhead injury disability claimants.…”
Section: Self-report Inventories and Pvt Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Nonsignificant trends were also observed for Fs and F-r. Finally, Tarescavage, Wygant, Gervais, and Ben-Porath (2013) found that higher scores on MMPI-2-RF overreporting scales, namely F-r and RBS, were associated with probable and definite Malingered Neurocognitive Dysfunction (MND; Slick, Sherman, & Iverson, 1999) in a large sample of nonhead injury disability claimants.…”
Section: Self-report Inventories and Pvt Performancementioning
confidence: 98%
“…On balance, the MMPI-2-RF literature supports the association between symptom overreporting and PVT failure. As noted above, however, only three studies to date have investigated the full range of MMPI-2-RF validity and substantive scales in relation to PVT performance (Gervais et al, 2011;Jones et al, 2012;Tarescavage et al, 2013), with only two of these studies exclusively examining individuals with external incentive (Gervais et al, 2011;Tarescavage et al, 2013). Importantly, the chief concern of these studies was investigating how self-report inventories can be used to enhance detection of inadequate effort.…”
Section: Self-report Inventories and Pvt Performancementioning
confidence: 99%
“…Further, WC patients may have financial incentives to remain disabled, and MMPI-2-RF research indicates that such financial incentives can be associated with over-reporting of emotional distress (cf. Gervais, Wygant, Sellbom, & Ben-Porath, 2011;Jones & Ingram, 2011;Schroeder et al, 2012;Tarescavage, Wygant, Gervais, & Ben-Porath, 2013;Wygant et al, 2011).…”
Section: Texas Back Institutementioning
confidence: 99%
“…Due to the heterogeneous symptoms often presented during these evaluations, it is important to capture elements of feigning across all areas of functioning. The MMPI-2 and MMPI-2-RF have been more thoroughly examined in relation to the criteria for MND and MPRD (Bianchini et al, 2008;Greve et al, 2006;Schroeder et al, 2012;Tarescavage et al, 2013;Wygant et al, 2011). In comparison, the PAI has much fewer studies examining the relation between its validity indicators with cognitive PVTs, MND, and MPRD.…”
Section: General Conclusion Concerning the Assessment Of Response Bimentioning
confidence: 97%